2021
DOI: 10.1186/s43141-021-00147-w
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of methylation status in MTHFR promoter region with recurrent pregnancy loss

Abstract: Background DNA methylation is an epigenetic process for modifying transcription factors in various genes. Methylenetetrahydrofolate reductase (MTHFR) stimulates synthesis of methyl radical in the homocysteine cycle and delivers methyl groups needed in DNA methylation. Furthermore, numerous studies have linked gene polymorphisms of this enzyme with a larger risk of recurrent pregnancy loss (RPL), yet scarce information is available concerning the association between epigenetic deviations in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Nevertheless, the mechanistic effect of DNA methylation in this area of the MTHFR gene expression is not completely clear. Previous studies showed that increased methylation was associated with suppression of gene expression [ 15 ] and disease conditions [ 15 , 70 , 71 ]. On the other hand, recent findings associated a reduction of MTHFR methylation with unfavorable conditions or diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the mechanistic effect of DNA methylation in this area of the MTHFR gene expression is not completely clear. Previous studies showed that increased methylation was associated with suppression of gene expression [ 15 ] and disease conditions [ 15 , 70 , 71 ]. On the other hand, recent findings associated a reduction of MTHFR methylation with unfavorable conditions or diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that imprinted gene defects lead to early pregnancy loss, fetal death, prolonged delivery, and the development of embryo tumors (56)(57)(58)(59). Liang et al found that the maintenance level of the imprinted gene PEGIO is very important for early embryo development, whose down-regulation leads to irreversible pregnancy loss (60). Zhang et al verified that the changes in the expression of imprinted genes and the hypermethylation profile of the repetitive regions (PRE-1 and satellite DNA) in cloned pigs may be related to the developmental defects and early pregnancy loss of the cloned pigs (61).…”
Section: Dna Methylation Of Imprinted Genes and Rplmentioning
confidence: 99%
“…Liang et al. found that the maintenance level of the imprinted gene PEGIO is very important for early embryo development, whose down-regulation leads to irreversible pregnancy loss ( 60 ). Zhang et al.…”
Section: Dna Methylation Of Imprinted Genes and Rplmentioning
confidence: 99%
“…One of the primary BDP features is the presence of a susceptible CpG Island (CGI) to DNA methylation (12). The promoters' methylation is associated with various diseases, and the level of CGI methylation is a further factor in the severity of the disease (12)(13)(14). In the current study, peripheral blood from FD patients from the same family carrying a GLA deletion mutation was used to investigate the possible accumulative effects of GLA deletion mutation with BDP methylation levels on the severity of the disease in FD patients and on the GLA and HNRNPH2 expression.…”
Section: Introductionmentioning
confidence: 99%